2015
DOI: 10.1017/jfm.2015.305
|View full text |Cite
|
Sign up to set email alerts
|

Diapycnal diffusivity, turbulent Prandtl number and mixing efficiency in Boussinesq stratified turbulence

Abstract: In order that it be correctly characterized, irreversible turbulent mixing in stratified fluids must distinguish between adiabatic ‘stirring’ and diabatic ‘mixing’. Such a distinction has been formalized through the definition of a diapycnal diffusivity, $K_{{\it\rho}}$ (Winters & D’Asaro, J. Fluid Mech., vol. 317, 1996, pp. 179–193) and an appropriate mixing efficiency, $\mathscr{E}$ (Caulfield & Peltier, J. Fluid Mech., vol. 413, 2000, pp. 1–47). Equivalent attention has not been paid to the definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
104
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 60 publications
15
104
1
Order By: Relevance
“…Such sensitivity is also observed in the results reported in both Hebert & de Bruyn Kops (2006a) and Hebert & de Bruyn Kops (2006b). More recently, de Bruyn Kops (2015) found that the dynamics of stratified flows are different at Gn = 48 and Gn = 220, which suggests another threshold at Gn ∼ O(100), consistent with the findings of Shih et al (2005) and Salehipour & Peltier (2015).…”
Section: Introductionsupporting
confidence: 81%
“…Such sensitivity is also observed in the results reported in both Hebert & de Bruyn Kops (2006a) and Hebert & de Bruyn Kops (2006b). More recently, de Bruyn Kops (2015) found that the dynamics of stratified flows are different at Gn = 48 and Gn = 220, which suggests another threshold at Gn ∼ O(100), consistent with the findings of Shih et al (2005) and Salehipour & Peltier (2015).…”
Section: Introductionsupporting
confidence: 81%
“…A constant mixing efficiency Ri f = 0.17 was assumed by Osborn (1980) leading to a mixing coefficient Γ = Ri f /(1 − Ri f ) = 0.2, a value which has been used in oceanographic applications ever since. More recently, Salehipour and Peltier (2015) have suggested to use the potential energy dissipation rate ǫ p instead of the buoyancy flux when calculating Γ because in steady-state stratified turbulence B = ǫ p and the irreversible conversion of available potential energy into background potential energy due to mixing is given by ǫ p . The potential energy dissipation rate is defined as ǫ p = (D/N 2 ) ∇b · ∇b since the Lindborg and Brethouwer (2008) who derive an analytical expression for the mean square particle displacement 1/2 δz 2 , which increases linearly in time with a constant of proportionality equal to K ρ .…”
Section: Introductionmentioning
confidence: 99%
“…Even if it is natural to expect that the dissipation rate of buoyancy and kinetic energy become independent from the value of molecular viscosity and diffusivity when they are sufficiently weak, numerical and laboratory experiments are often performed in intermediate regimes for which those parameters may influence the mixing efficiency, see e.g. Shih et al (2005); Lozovatsky & Fernando (2013) ;Bouffard & Boegman (2013); Salehipour & Peltier (2015).…”
Section: Comparison With Previous Studies Of the Efficiency Of Mixingmentioning
confidence: 99%
“…Winters et al (1995); Peltier & Caulfield (2003); Davis Wykes et al (2015); Salehipour & Peltier (2015) and references therein. The traditional approach involves direct analyses of the diffusive destruction of smallscale density variance as the experiment proceeds, which in turn requires a separation of the influence of stirring from that of irreversible mixing through application of the Lorenz concept of available potential energy that can be converted into kinetic energy and a base-state potential energy which can not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation